KONTRIBUSI MOTIVASI INTRINSIK DAN SELF-EFFICACY TERHADAP SELF-REGULATION - Lati Fatul Husna; Muhamad Uyun (Jurnal RAP (Riset Aktual Psikologi Universitas Negeri Padang), 2025)
This study aims to examine the relationship between intrinsic motivation and self-efficacy with self-regulation in Jakabaring Fitness members in Palembang City. The research subjects consisted of 60 active fitness members. The method used was quantitative correlation with total sampling technique. The results of the analysis showed that intrinsic motivation and self-efficacy are predictors of self-regulation, with a value of F = 21.181 (p <0.01). These two factors play a positive role in self-regulation, indicating that the higher the intrinsic motivation and self-efficacy, the better individuals are at regulating and maintaining their exercise habits. Simultaneously, intrinsic motivation and self-efficacy contributed 40.6% to self-regulation. While partially intrinsic motivation increases self-regulation by 0.461, while self-efficacy increases by 0.264.